Use of Precise Area Fraction Model for Fine Grid DEM Simulation of ICFB with Large Particles - Gruorong Wu (Symmetry, 2020)
The heterogeneous structures in a gas−solid fluidized bed can be resolved in discrete element simulation so long as the grid is fine enough. In order to conveniently calculate mean porosity in fine grid simulations, a precise area fraction model is given for two-dimensional simulations. The proposed area fraction model is validated by the discrete element simulation test on a small-scale internal circulation fluidized system of large particles, using a fine grid size of two particle diameters. Simulations show that the discrete element method can perform well in modelling time-varying waveforms for the physical quantities in an internal circulating fluidized bed, employing the precise gas area fraction model. This thought of precise calculation can be generalized to construct a volume fraction porosity model for three-dimensional simulation by use of the similar symmetry of a rectangular grid. Moreover, to construct these area and volume fraction models is to enrich and perfect the underlying model of fine grid simulation.